2015
DOI: 10.17051/io.2015.63115
|View full text |Cite
|
Sign up to set email alerts
|

İlkokul öğrencilerinin proje tabanlı öğrenme tutumlarına yönelik bir ölçek geliştirme çalışması

Abstract: ABSTRACT. The purpose of this research is to develop an attitude scale which intends to measure primary school students' attitudes towards Project Based Learning. A 30 item trial form of the Project Based Learning Attitude Scale was constructed. For this, related literature was reviewed for the learning outcomes of Project Based Learning and these outcomes were used for the construction of the items of the scale. The trial form was administered to totally 698 participants who were fourth grade primary school s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The RMR value refers to the absolute difference between the observed covariance and the covariance predicted by the model. If this value is equal to or smaller than 0.05, the it is considered to be acceptable [49]. In the current study this value was found to be 0.038.…”
Section: The Technology and Environmental Ethics Questionnairementioning
confidence: 54%
“…The RMR value refers to the absolute difference between the observed covariance and the covariance predicted by the model. If this value is equal to or smaller than 0.05, the it is considered to be acceptable [49]. In the current study this value was found to be 0.038.…”
Section: The Technology and Environmental Ethics Questionnairementioning
confidence: 54%